Pengembangan Bahan Ajar Tata Rias Pengantin Solo Putri - Mochamad Noor Hendra; Subandowo; Yoso Wiyarno (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2020)
The role of vocational education in generating employment has been prevalent throughout modern times. However, fewer studies have discussed the development process of vocational teaching materials, from validations to applications. This article contributed to the discussion of the material development and validation in Traditional Wedding Makeup, Solo style’s course in Universitas PGRI Adi Buana, Surabaya, Indonesia. The results of this study supported the applicability and validity of the developed teaching materials. Explicitly, expert designers agreed on the use of contents by 90%, while peer-lecturers concurred by 95%. The result implied the usability and applicability in the classroom.